Diagnosis of intrapreneurship-based professionalism to bridging the Culture Gap Innovation approach - DJASTUTI, I; KUSUMAWARDHANI, A; MAHFUDZ, M; UDIN, U (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to analyze the attitude of the entrepreneur orientation of the company’s employee auxiliaries (EOS) and the attitude of entrepreneur leadership (ELQ) employees of the target company with importance-performance analysis (IPA). The samples are employees who have a business which is determined using non-probability sampling techniques. The data are analyzed by applying structural equation modelling (SEM) with 24 AMOS program. The findings of the study using the IPA approach show that there is no gap between perception and expectation of the respondents. RESUMEN Este estudio tiene como objetivo analizar la actitud de la orientación emprendedora de los auxiliares de empleados de la empresa (EOS) y la actitud de los empleados de liderazgo emprendedor (ELQ) de la empresa objetivo con el análisis de importancia-desempeño (IPA). Las muestras son empleados que tienen un negocio que se determina utilizando técnicas de muestreo no probabilístico. Los datos se analizan mediante la aplicación de modelos de ecuaciones estructurales (SEM) con el programa 24 AMOS. Los resultados del estudio que utiliza el enfoque IPA muestran que no existe una brecha entre la percepción y las expectativas de los encuestados.